2021
DOI: 10.1002/smll.202006229
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Visualization of the Structural Evolution and Alignment of Lyotropic Liquid Crystals in Confined Flow

Abstract: Self‐assembled materials such as lyotropic liquid crystals offer a wide variety of structures and applications by tuning the composition. Understanding materials behavior under flow and the induced alignment is wanted in order to tailor structure related properties. A method to visualize the structure and anisotropy of ordered systems in situ under dynamic conditions is presented where flow‐induced nanostructural alignment in microfluidic channels is observed by scanning small angle X‐ray scattering in hexagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Buscema and coworkers [115] employed a contraction device to explore the flow-induced structural changes of liposomes. Very recently, Rodriguez-Palomo et al [116] employed SAXS to study the structure of lyotropic liquid crystals and their behaviour in contraction microfluidic devices. Few other studies were also reported to explore the flow behaviour of complex fluids in geometries substantially different from the contraction one, including serpentine channels and microfluidic pillars [111,117].…”
Section: Microfluidic Rheometry Integrated To Sans and Saxsmentioning
confidence: 99%
“…Buscema and coworkers [115] employed a contraction device to explore the flow-induced structural changes of liposomes. Very recently, Rodriguez-Palomo et al [116] employed SAXS to study the structure of lyotropic liquid crystals and their behaviour in contraction microfluidic devices. Few other studies were also reported to explore the flow behaviour of complex fluids in geometries substantially different from the contraction one, including serpentine channels and microfluidic pillars [111,117].…”
Section: Microfluidic Rheometry Integrated To Sans and Saxsmentioning
confidence: 99%
“…It is worth also noting that the flow strains and the employed shear stresses in microfluidics may lead to the alignment of vesicles and affect the orientation of lamellar and hexagonal phases under shear flow, resulting in the appearance of anisotropic SAXS (or SANS) patterns [ 31 , 71 , 74 , 79 ]. For instance, a slight alignment was detected during the microfluidic synthesis of MLVs on increasing TFR from 5 to 15 μL/min ( Figure 4 A,B).…”
Section: Continuous Production and In Situ Characterization Of Nano-s...mentioning
confidence: 99%
“…A shear-induced deformation of MLVs was also detected under shear flow during their formation from a lamellar phase [ 79 ]. Through a microfluidic SAXS scanning study, Liebi and co-workers [ 74 ] reported on the flow-induced transformation of the lamellar (L α ) phase to an aligned lamellae region via MLVs to an extended lamellae region by increasing the shear rates ( Figure 4 D). A significant effect of the microfluidic constriction, leading to an orientation of the lamellar phase under flow, was also reported ( Figure 4 E,F) in another study [ 71 ].…”
Section: Continuous Production and In Situ Characterization Of Nano-s...mentioning
confidence: 99%
See 2 more Smart Citations